2011
DOI: 10.4244/eijv7i7a129
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting, what can be learned after more than 1,000 patients: a single centre single operator experience

Abstract: In a high-volume experienced centre, the in-hospital complication rate is low. Complications occurred almost exclusively in patients with unfavourable anatomical or procedural characteristics and seem to be avoidable in most patients. A learning curve was observed up to 500 procedures. Elderly patients have a higher complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Variations of these factors could impact the results (14,19). A significant reduction in the incidence, the number, and the volume of new cerebral ischemic lesions was found in patients who underwent CAS with proximal balloon compared with filter protection.…”
Section: Dw-mri Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Variations of these factors could impact the results (14,19). A significant reduction in the incidence, the number, and the volume of new cerebral ischemic lesions was found in patients who underwent CAS with proximal balloon compared with filter protection.…”
Section: Dw-mri Findingsmentioning
confidence: 94%
“…Carotid artery stenting was performed by a single experienced operator (J.S.) (14) as described in detail previously (11). The protocol specified use of the Cristallo ideale stent (Invatec, Roncadelle, Italy), the Emboshield Protection System for filter protection (Abbott Vascular, Abbott Park, Illinois), and the MO.MA ultra system (Invatec) for proximal balloon occlusion, respectively.…”
Section: Study Design the Profi (Prevention Of Cerebral Embolizationmentioning
confidence: 99%
“…Bijuklic et al [37] achieved this by analyzing surgical performance data at a high carotid artery stenting (CAS) volume center and found that the inhospital complication rates fell to 3% and 1% after 100 and 500 procedures, respectively.…”
Section: Vascular Surgerymentioning
confidence: 98%
“…16 Some high-volume centers report lower event rates in their real-world populations of symptomatic and asymptomatic patients (range from 1.7% to 4.7%). 7,8,[17][18][19][20] However, 3 major issues need to be considered when comparing the current results with older reports. First, a strict, independent neurological assessment before and after the procedure was not mandatory in previous trials and even less so in registries.…”
Section: Procedural Outcomementioning
confidence: 84%
“…Such registries have already shown comparable results of CAS and CEA. [7][8][9][10] However, most of the previous registry data are limited with respect to the accuracy or completeness of patient surveillance, the length of follow-up, or patient number.…”
mentioning
confidence: 99%